Wrestling with God : Jewish theological responses during and after the Holocaust - Katz, Steven T., 1944-; Biderman, Shlomo; Greenberg, Gershon (Oxford University Press, 2007)
This volume presents a wide-ranging selection of Jewish theological responses to the Holocaust. It will be the most complete anthology of its sort, bringing together for the first time: (1) a large sample of ultra-orthodox writings, translated from the Hebrew and Yiddish; (2) a substantial selection of essays by Israeli authors, also translated from the Hebrew; (3) a broad sampling of works written in English by American and European authors. These diverse selections represent virtually every significant theological position that has been articulated by a Jewish thinker in response to the Holo.